2021
DOI: 10.1371/journal.pone.0245473
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic-related attitudes, stressors and work outcomes among medical assistants during the SARS-CoV-2 (“Coronavirus”) pandemic in Germany: A cross-sectional Study

Abstract: Background The SARS-CoV-2 virus has spread rapidly around the globe since December 2019 creating much uncertainty among medical staff. Due to close patient contact, medical assistants are at increased risk of an infection. Several studies have investigated psychological consequences of the SARS-CoV-2 pandemic on medical staff, yet studies in the outpatient setting are scarce and studies addressing medical assistants are lacking. This study aimed to investigate pandemic-related stressors, attitudes, and work ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 23 publications
(25 reference statements)
1
31
0
Order By: Relevance
“…Gender may be a significant factor for psychological stress during the epidemic, and female medical staff was at great risk of poor psychological health. Several studies among medical staff during the SARS-CoV-2 pandemic have indicated that women reported more severe symptoms of depression, anxiety, and distress than men (32)(33)(34). In general, women's physical ability is not as good as men's, and the excessive workload inevitably leads to women's greater anxiety than men.…”
Section: Discussionmentioning
confidence: 99%
“…Gender may be a significant factor for psychological stress during the epidemic, and female medical staff was at great risk of poor psychological health. Several studies among medical staff during the SARS-CoV-2 pandemic have indicated that women reported more severe symptoms of depression, anxiety, and distress than men (32)(33)(34). In general, women's physical ability is not as good as men's, and the excessive workload inevitably leads to women's greater anxiety than men.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, for HCWs home-work interface was found as a cause of stress and also contributed to the development of burnout symptoms [46,47]. Major concerns included childcare [22,46,48,49], household activities and the relationships with family and friends [50,51]. During this time of emergency HCWs experienced a significantly lower work-family balance due to long working hours without appropriate rest [52], which was particularly challenging for women as they tended to be more involved in family care [49].…”
Section: Home-work Interface and Balancementioning
confidence: 99%
“…Major concerns included childcare [22,46,48,49], household activities and the relationships with family and friends [50,51]. During this time of emergency HCWs experienced a significantly lower work-family balance due to long working hours without appropriate rest [52], which was particularly challenging for women as they tended to be more involved in family care [49]. Moreover, the fear of bringing contagion home to family members was a common issue contributing to occupational stress, anxiety and depression symptoms in HCWs [53].…”
Section: Home-work Interface and Balancementioning
confidence: 99%
See 2 more Smart Citations